2013
DOI: 10.1177/1045389x13476147
|View full text |Cite
|
Sign up to set email alerts
|

Electrical discharge machining characteristics of nickel–titanium shape memory alloy based on full factorial design

Abstract: Among many shape memory alloys, nickel-titanium (NiTi) alloys are popular due to their superior properties in shape memory effect and superelasticity. They are presently often used in microengineering and medical technology especially in orthopedic and orthodontic implants due to their specific properties. In this study, the electric discharge machine characteristics of NiTi shape memory alloys have been fully investigated by full factorial design. Analysis of mean showed that the material removal rate of NiTi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…The formation of the alloy compounds observed from the XRD analysis, which in turn causes higher surface hardness. These findings also support the investigations carried out by Alidoosti et al 16 From Fig. 8(b), it is observed that for a fixed pulse on time of 120 ls, pulse off time of 62 ls, and for varying SV the CuZn peak intensity reduced to very low and some peaks are disappeared.…”
Section: B Effects Of Parameters On Surface Roughness (R a )supporting
confidence: 94%
See 1 more Smart Citation
“…The formation of the alloy compounds observed from the XRD analysis, which in turn causes higher surface hardness. These findings also support the investigations carried out by Alidoosti et al 16 From Fig. 8(b), it is observed that for a fixed pulse on time of 120 ls, pulse off time of 62 ls, and for varying SV the CuZn peak intensity reduced to very low and some peaks are disappeared.…”
Section: B Effects Of Parameters On Surface Roughness (R a )supporting
confidence: 94%
“…The layer may exhibit hard brittle nature, stresses caused to produce cracks. 16 C. XRD analysis of SMA after WEDM process Fig. 8(a), for a fixed higher pulse off time and SV, the TiNiCu peak intensity is decreasing with increase in pulse on time.…”
Section: B Effects Of Parameters On Surface Roughness (R a )mentioning
confidence: 98%
“…It was also interesting to note that EDM instruments did not exhibit surface pollution from the EDM electrode materials (e.g. Cu or Cu-W alloys), a defect reported for ED-machined NiTi wires (Alidoosti et al 2013). This observation proved the high quality of the manufacturing process of these instruments.…”
Section: Surface Structurementioning
confidence: 60%
“…Cu or Cu‐W alloys), a defect reported for ED‐machined NiTi wires (Alidoosti et al . ). This observation proved the high quality of the manufacturing process of these instruments.…”
Section: Discussionmentioning
confidence: 97%
“…The drawbacks of laser cutting can be overcome by electro discharge machining (EDM), which allows similar tolerances but avoiding HAZ because the melting is promptly followed by an almost instantaneous vaporization of the material. 31 Some contaminants are, however, present on the cuts surface because of the used dielectric medium and the Cu electrode. The EDM limits are mainly because of the low productivity and the width of the cut that is directly related to the electrode diameter: 0.1e0.3 mm.…”
Section: Machining and Cuttingmentioning
confidence: 99%